CYBERSECURITY ANALYSIS IN THE CONTEXT OF THE RUSSIA-UKRAINE CONFLICT: CHALLENGES, THREATS, AND DEFENSE STRATEGIES - Imam Budiman; Arliya Fadya Salsabila; Chandra Izat Mubarok; Naura Fasya Rustiawan; Rinaldi Anwar Zulfikar (SEAN Institute, 2023)
The role of cybersecurity in the context of the conflict between Russia and Ukraine has become a concern for the international community due to its widespread impact on national security and regional stability. Cyber attacks have become a significant tool in modern conflicts, and this research aims to understand the role of cybersecurity in the escalation of the conflict between Russia and Ukraine. The role of cybersecurity in this conflict involves cyber attacks carried out by Russia against Ukraine's critical infrastructure. These attacks include targeting Ukraine's communication, power, and financial systems. These attacks have had a significant impact on Ukraine's ability to resist Russian invasion and maintain their national security. Additionally, this paper discusses Ukraine's efforts to strengthen their cyber defense in response to the cyber attacks by Russia. Steps taken by Ukraine include enhancing their cyber defense capabilities, cooperation with international partners, and increasing public awareness of cyber threats. This paper also analyzes the international community's response to cyber attacks in the context of the Russia-Ukraine conflict. International organizations such as NATO and the European Union play a crucial role in providing support and technical assistance to Ukraine in combating cyber attacks by Russia. However, the challenges faced in addressing the evolving cyber threats require stronger cooperation among countries worldwide.